Increased expression of the ATP‐gated P2X7 receptor reduces responsiveness to anti‐convulsants during status epilepticus in mice. (4th February 2022) - Beamer, Edward; Morgan, James; Alves, Mariana; Menéndez Méndez, Aida; Morris, Gareth; Zimmer, Béla; Conte, Giorgia; de Diego‐Garcia, Laura; Alarcón‐Vila, Cristina; Yiu Ng, Nico Ka; Madden, Stephen; Calzaferri, Francesco; et al.
Abstract : Background and Purpose: Refractory status epilepticus is a clinical emergency associated with high mortality and morbidity. Increasing evidence suggests neuroinflammation contributes to the development of drug‐refractoriness during status epilepticus. Here, we have determined the contribution of the ATP‐gated P2X7 receptor, previously linked to inflammation and increased hyperexcitability, to drug‐refractory status epilepticus and its therapeutic potential. Experimental Approach: Status epilepticus was induced via a unilateral microinjection of kainic acid into the amygdala in adult mice. Severity of status epilepticus was compared in animals with overexpressing or knock‐out of the P2X7 receptor, after inflammatory priming by pre‐injection of bacterial lipopolysaccharide (LPS) and in mice treated with P2X7 receptor‐targeting and anti‐inflammatory drugs. Key Results: Mice overexpressing P2X7 receptors were unresponsive to several anticonvulsants (lorazepam, midazolam, phenytoin and carbamazepine) during status epilepticus. P2X7 receptor expression increased in microglia during status epilepticus, at times when responses to anticonvulsants were reduced. Overexpression of P2X7 receptors induced a pro‐inflammatory phenotype in microglia during status epilepticus and the anti‐inflammatory drug minocycline restored normal responses to anticonvulsants in mice overexpressing P2X7 receptors. Pretreatment of wild‐type mice with LPS increased P2X7 receptor levels in the brain and reduced responsiveness to anticonvulsants during status epilepticus, which was overcome by either genetic deletion of P2X7 receptors or treatment with the P2X7 receptor antagonists, AFC‐5128 or ITH15004. Conclusion and Implications: Our results demonstrate that P2X7 receptor‐induced pro‐inflammatory effects contribute to resistance to pharmacotherapy during status epilepticus. Therapies targeting P2X7 receptors could be novel adjunctive treatments for drug‐refractory status epilepticus. Abstract :